COMBINING DATA ENVELOPMENT ANALYSIS AND ANALYTIC HIERARCHY PROCESS FOR EFFICIENT INLAND PORT SERVICES: CASE STUDY OF THE PORT DUNAV PANCEVO - Pjevcevic, Danijela; Dimitrijevic, Branka; Vukicevic Bisevac, Ivana; Vukadinovic, Katarina (International Journal of Industrial Engineering: Theory, Applications and Practice, 2018)
This paper shows the process of decision making in order to choose the most efficient technology for dry bulk cargo handling at an inland port. The port operator's objective is to maximize the efficiency of cargo handling services, in order to primarily minimize total vessel time in the port. Proposed combinations of major and auxiliary handling equipment, vehicles, and corresponding labour, together with dry bulk cargo packing options are systematized into 16 variants defined by a survey from experts in the field. We proposed a three-step approach to select the most efficient among them. In the first step we used simulation to obtain performance indicators for each variant. In the second step, AHP is used to quantify qualitative data. Finally, the CCR DEA model and super-efficiency DEA modelare used to identify the most efficient variant(s).